Hydrological Analysis of Loess Plateau Highland Control Schemes in Dongzhi Plateau - Huo, Aidi; Peng, Jianbing; Cheng, Yuxiang; Luo, Pingping; Zhao, Zhixin; Zheng, Chunli (Frontiers in Earth Science, 2020)
Gully Consolidation and Highland Protection (GCHP) Project is a major soil and water conservation and land remediation project implemented in the Chinese Loess Plateau (CLP). As the connection between the mechanisms of erosion and practical applications for addressing it is not clear, the implementation of engineering measures to combat the problem has been insufficient to date. This study used field investigation and descriptive statistics, together with hydrological analysis modeling to gain an understanding of the impact of the Loess Plateau Highland Control Schemes on the evolution of the Dongzhi Plateau as the largest, most well-preserved, and the thickest loess deposit region in China. A remote sensing image was introduced to hydrological modeling to prove the analysis results of the Dongzhi Plateau. According to these investigations and analysis, four major schemes of gully head retrogressive erosion control were summarized and a comprehensive theory and technology based on a watershed were proposed. After hydrological analysis, the Dongzhi Plateau was divided into 1225 watersheds. It was found that GCHP should be implemented in the catchment area based on hydrological analysis to solve the problem of retrogressive erosion, and it is recommended that a scientific and rational drainage system should be designed based on the roads and pipe networks in the whole watershed area. Findings from this paper provide insights into the evolution of CLP and it can give a good suggestion on the future implementation of GHCP.